2019
DOI: 10.1016/j.hjc.2018.03.001
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of CHA2DS2-VASc and GRACE risk scores in patients with ACS

Abstract: In our study, The CHADS-VASc score managed to predict, marginally better, the appearance of MACCE over GRACE, in patients with angioplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Peng et al found that MACE during hospitalization and long-term follow-up increased when the CHA 2 DS 2 -VASc score increased, and the CHA 2 DS 2 -VASc score exhibited independent predictive value for MACE ( 3 ). The other study demonstrated that the predictive value of the CHA2DS2-VASc score for all-cause mortality and cardiovascular mortality is marginally greater than that of the GRACE score ( 23 ). Our investigation demonstrated that R 2 -CHA 2 DS 2 -VASc ≥ 3 is the optimum cut-off value for predicting MACE with a sensitivity of 50% and a specificity of 91.1%.…”
Section: Discussionmentioning
confidence: 89%
“…Peng et al found that MACE during hospitalization and long-term follow-up increased when the CHA 2 DS 2 -VASc score increased, and the CHA 2 DS 2 -VASc score exhibited independent predictive value for MACE ( 3 ). The other study demonstrated that the predictive value of the CHA2DS2-VASc score for all-cause mortality and cardiovascular mortality is marginally greater than that of the GRACE score ( 23 ). Our investigation demonstrated that R 2 -CHA 2 DS 2 -VASc ≥ 3 is the optimum cut-off value for predicting MACE with a sensitivity of 50% and a specificity of 91.1%.…”
Section: Discussionmentioning
confidence: 89%
“…The components of these two scores are associated with atherosclerosis, vascular spasm, and microvascular dysfunction, which overlap the risk factors of NRP [7]. Several recent studies have also shown that the CHA 2 DS 2 -VASc scores are associated with the severity of coronary artery disease, its prognosis, and NRP in patients with acute MI, contrast-induced nephropathy after PPCI for acute coronary syndrome, in-stent restenosis, acute stent thrombosis, mechanical mitral valve thrombosis, and right ventricular dysfunction [8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 98%
“…The CHA 2 DS 2 -VASc (congestive heart failure, hypertension, age, diabetes mellitus, stroke, vascular disease and sex) score is a simple risk stratification scheme to estimate stroke/thromboembolic risk in patients with nonvalvular atrial fibrillation (AF). 18 Recent studies have reported that the CHA 2 DS 2 -VASc score could predict adverse clinical outcomes in stable coronary artery disease, acute coronary syndrome (ACS), 19 or patients undergoing revascularization, 20,21 independent of the presence of AF. [22][23][24] However, it remains unknown whether this score system has the ability to predict ischemic events in patients who underwent PCI.…”
Section: Introductionmentioning
confidence: 99%